Cultural heritage in the crosshairs : protecting cultural property during conflict - Kila, Joris.; Zeidler, James A., 1949- (Heritage and Identity, 2013)
The protection of cultural property during times of armed conflict and social unrest has been an on-going challenge for military forces throughout the world even after the ratification and implementation of the 1954 Hague Convention and its two Protocols by participating nations. This volume provides a series of case studies and "lessons learned" to assess the current status of Cultural Property Protection (CPP) and the military, and use that information to rethink the way forward. The contributors are all recognized experts in the field of military CPP or cultural heritage and conflict, and all are actively engaged in developing national and international solutions for the protection and conservation of these non-renewable resources and the intangible cultural values that they represent.